Dual-wavelength photodetector based on layered WSe2/n-GaN van der Waals heterostructure. (March 2023) - Ye, B.J.; Liu, Y.S.; Xie, F.; Yang, X.F.; Gu, Y.; Zhang, X.M.; Qian, W.Y.; Zhu, C.; Lu, N.Y.; Chen, G.Q.; Yang, G.F.
Abstract: Van der Waals (vdW) heterojunction photodetectors based on two-dimensional (2D) materials have been widely used in the field of optoelectronics. However, so far, there are few studies on 2D materials with type I energy band alignment. In this work, layered tungsten selenide (WSe2 ) is transferred on the prepared gallium nitride (GaN) substrate by mechanical exfoliation method. The morphology and optical properties of layered WSe2 are characterized by atomic force microscope (AFM) and spectrum. Besides, the current–voltage ( I–V) characteristics, photoresponses, and transient photoresponses of the photodetector based on WSe2 /GaN heterojunction are investigated, it is found that the device shows good rectifying behavior and dual-wavelength photoresponse. Furthermore, the density functional theory (DFT) calculations verify the type I energy band alignment of the WSe2 /GaN heterojunction and exhibit the enhanced optical absorption corresponding to the photoresponse band. This work demonstrates that the WSe2 /GaN heterojunction photodetector based on the mechanical exfoliation method holds potential for the application of optoelectronic devices.